2018
DOI: 10.1037/ccp0000291
|View full text |Cite
|
Sign up to set email alerts
|

Individualized motivational plans in batterer intervention programs: A randomized clinical trial.

Abstract: These results highlight the relevance of alternative approaches, including strategies to increase treatment compliance and motivation for change, in BIPs. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
151
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 89 publications
(157 citation statements)
references
References 62 publications
5
151
1
Order By: Relevance
“…IPV perpetrators were recruited from the participants in a psycho‐educational and community‐based treatment programme (mandatory for male abusers). Because they were sentenced to <2 years in prison and had no previous criminal record, participants had been given a suspended sentence on the condition that they would attend an intervention programme (Lila et al ., ). The inclusion criteria for controls included: males over 18 years of age with no physical or mental problems, no severe substance abuse problems and no severe cognitive impairment.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…IPV perpetrators were recruited from the participants in a psycho‐educational and community‐based treatment programme (mandatory for male abusers). Because they were sentenced to <2 years in prison and had no previous criminal record, participants had been given a suspended sentence on the condition that they would attend an intervention programme (Lila et al ., ). The inclusion criteria for controls included: males over 18 years of age with no physical or mental problems, no severe substance abuse problems and no severe cognitive impairment.…”
Section: Methodsmentioning
confidence: 97%
“…(2016) were unable to identify a specific part of the intervention that improved these cognitive abilities. Although this intervention did not contain specific cognitive training designed to improve cognitive abilities, participants received training in cognitive restructuring, emotion management skills and problem‐solving, among others (Lila et al ., ), which may explain these improvements. In this regard, some studies have demonstrated that problem‐solving training would improve these abilities in different populations through slower and controlled processing, step by step (Kurowski et al ., ; Romero‐Martínez et al ., ).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, high impulsivity and inattention symptoms have been related to high levels of emotion decoding and cognitive flexibility impairments in violent populations (Buitelaar et al, 2014;Saylor & Amann, 2016;Wymbs et al, 2017). IPV perpetrators had been sentenced to less than 2 years in prison but had no previous criminal record, and hence they had their sentence suspended on the condition that they attend an intervention like the CONTEXTO program (Carbajosa, Catalá-Miñana, Lila, & Gracia, 2017;Lila, Catalá-Miñana, & Gracia, 2018;Rodriguez, Gracia, & Lila, 2016). Moreover, we expected that the relationship between emotion decoding and cognitive flexibility deficits would be stronger with inattention than trait impulsivity in both populations, as previously suggested (Gamboz, Borella, & Brandimonte, 2009;.…”
mentioning
confidence: 99%